FDI and Export Performance in the Textile Industry : Comparing Turkey and India - Barinova, Mariia; Proch, Dominik; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis examines the relationship between foreign direct investment (FDI) and export performance in the textile industries of Turkey and India over the past ten years. Its main objective is to explain why strong export performance in both countries has not been accompanied by proportionally high FDI inflows into the textile sector. The study combines a structured literature review with descriptive and comparative analysis of macroeconomic conditions and the structural characteristics of the textile industry and an empirical assessment of the investment climate, FDI patterns and export performance. The empirical part draws on secondary data from international organizations and national statistics and is complemented by case studies of selected FDI projects in the textile value chains of Turkey and India. The findings confirm that both countries rank among the world’s leading textile exporters and maintain persistent trade surpluses in this sector, while textiles consistently attract less than 2% of total FDI inflows. The analysis shows that high export performance alone is insufficient to attract substantial FDI when macroeconomic stability, institutional quality, sectoral structure, cost competitiveness and investment incentives do not align with investor expectations. In both Turkey and India, macroeconomic and institutional constraints, structural features of the textile industry, relative cost disadvantages and policy misalignments weaken the expected complementarity between FDI and exports. The thesis concludes that the relationship between FDI and export performance in the textile sector is conditional rather than automatic and that leveraging FDI more effectively for upgrading in labor-intensive manufacturing requires targeted institutional and sector-specific reforms.
Vedoucí práce: Dominik Proch
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses